Student evaluations of teaching are an inadequate assessment tool for evaluating faculty performance - Hornstein, Henry A. (Cogent education, 2017)
Literature is examined to support the contention that student evaluations of teaching (SET) should not be used for summative evaluation of university faculty. Recommendations for alternatives to SET are provided.